Post-Stroke Rehabilitation - Sanchetee, Pratap (IntechOpen, 2022)
Stroke continues to be a major public health issue. It is the third leading cause of death and disability across the globe. Its early identification, early treatment, and prevention are major issues that confront a treating physician. This book addresses the common clinical problems encountered by a stroke rehabilitation team. Stroke survivors are left with a myriad of deficits including motor weakness, sensory and perceptual deficits, speech and swallowing impairment, cognition deficits, and behavioral problems. These topics are dealt with in detail by experts with the goal of disability reduction and functional rehabilitation. This book provides in-depth knowledge on the rehabilitation measures for stroke-related impairments including motor deficits, cognitive impairment, and psychological problems.